Diagnostic Value of Different Biomarkers to Identify Bacterial Coinfection in Vietnamese Children with Severe Rhinovirus Pneumonia - Pham, Hien Thu; Nguyen, Tran Thi Ngoc; Thi Tam, Ngo (Journal of Child Science, 2020)
This study aims to assess the diagnostic value of high-sensitivity C-reactive protein (hs-CRP), procalcitonin (PCT), and interleukin (IL)-6 in the diagnosis of pneumonia caused by Rhinovirus alone or with bacterial coinfection in Vietnamese children under 5 years of age. A cross-sectional study was conducted on 26 children under 5 years of age with severe pneumonia due to Rhinovirus at the National Pediatric Hospital. IL-6, hs-CRP, and PCT tests were performed. The diagnostic values of PCT, IL-6, and hs-CRP in classifying those with viral alone and those with bacterial coinfection were determined. Of 26 children, 10 children were diagnosed to have bacterial coinfections (38.5%). The optimal cutoff point for PCT was > 2.30 ng/mL (sensitivity 50%, specificity 94%, positive predictive value 83%, and negative predictive value 75%). The optimal cutoff point for hs-CRP was > 1.53 mg/dl (sensitivity 90%, specificity 56%, positive predictive value 56%, and negative predictive value 90%). Finally, the optimal cut-off point for IL-6 was > 441.5 pg/mL (sensitivity 20%, specificity 100%, positive predictive value 100%, and negative predictive value 60%). The accuracy rate of PCT was the highest with 69.2%, followed by hs-CRP with 65.4%. Inflammatory biomarkers such as PCT and hs-CRP were able to distinguish children with severe pneumonia caused by Rhinovirus alone and those with bacterial coinfection.
Keywords: respiratory syncytial virus; pneumonia; procalcitonin; bacterial coinfections